Анализ нагрузок при разрушении горных пород алмазно-твердосплавными пластинами - Бочковский, А.М.; Коростышевский, Д.Л. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
The method of application of a level detection of offloading on diamond stratum PDC is resulted,
outcomes of a trial of laminas with a figurate emulsion carrier on a shearing are introduced,
its advantage in comparison with serial with a plane substrate of an emulsion carrier is displayed.